Desarrollo de identidad de marca, diseño de producto y piezas comunicacionales para PIXMAP - Zlatar Cáceres, Ivanna Paula (2021)
This document consists on the development of brand identity, product design, and the creation of communication pieces for Pixmap, an application that uses computer vision to predict the areas of greatest attention to an image. This document also embodies the identification of distinctive concepts of the brand, the definition of communication pillars and the execution of the strategic plan on Instagram, with the aim of increasing brand awareness during its pre-market launch stage. The derived results demonstrate a reach of 1,900 impressions of the product in the iOS App Store, 213 downloads, a conversion rate of 5% and a reach of 146 organic followers on the brand's Instagram page after a five-week strategy. It is emphasized that the brandbook, beyond its informative function, fulfills a guiding role for following the established graphic narrative and takes part in the continuous graphic manifestation of Pixmap. Finally, it is evidenced the importance of the development of an identity manual to maintain consistency in the design of the product and in the communication pieces that contribute to the instant recognition of the brand.